Best innovators develop a point of view on the future and a roadmap on how to get there. Issue 2 (16th March 2015) - Engel, Kai; Dirlea, Voletka; Dyer, Stephen; Graff, Jochen
Abstract : Purpose: – The authors have collected key insights from the Best Innovator competition, launched in 2003. Six early-stage practices are critical. Design/methodology/approach: – The Best Innovator competition, annual benchmarking against the best in innovation management, focuses on the how-to of innovation and examines what leading companies are doing to achieve better yield with their innovation strategies. Findings: – By studying the competition winners, the researchers found a strong correlation between specific innovation management practices and sustainable, profitable growth. Practical implications: – Best Innovators establish explicit expectations for making the business case for innovation. They name a specific set of deliverables to which they are committed. Originality/value: – The article offers specific guidelines for setting the stage for continuous innovation that results in profitable offerings and services.